Metode Stimulasi dan Perkembangan Emosi Anak Usia Dini - Wisjnu Martani (Jurnal Psikologi, 2012)
Emotion is an important factor for early child life. Children use their emotion to be able to be survive. One of the factors in early child emotion development is teacher. The technique to stimulate depends on the teacher understanding to the child development and the stimulation it self. This research was aimed to investigate how extent the teacher understanding was implemented in the stimulation technique for early children emotional development. The participants were 30 kindergarten teachers. Data was collected using interview and opened questionary. Data was analyzed through qualitative approach. The result shows that teacher understands the children emotional development, but the stimulation way is based on the manner set and teacher perception. Keywords: teacher perception, early children, stimulation, emotional development